UM ESTUDO COMPARATIVO ENTRE MODELOS DE GERENCIAMENTO DE RISCO DE PROJETOS - Marques, Antonio Augusto Barbosa (2008)
The objective of this work was to make a comparison between PMI s model for project risk management, presented in the Project Management Body of Knowledge (PMBoK®), and the standard for risk management released by the Standard Australia together with the Standard New Zeland, referred as standard AS/NZS 4360:2004, establishing its points of convergence and also its points of divergence. To achieve that, an extensive bibliographic revision was made, seeking to fundament the main concepts involved with strategic organization, projects, uncertainty, risk and risk management. By the end of the research, it was possible to observe that the models analyzed were equivalent in their risk treatment phase, first establishing a reference with the stakeholders aligned with the organization s tolerance, and then planning how to take care of the risks throughout the project s life cycle. It was also possible to observe the occurrence of qualitative analysis phase, supported by a methodology that indicated the need of a preliminary filtering phase, followed by a quantitative analysis phase, both intended to control the most relevant variables that affect the risk. The few divergences observed were related with the occurrence of an explicit step for risk evaluation, within the AS/NZS 4360:2004 standard, when in the PMI s model, the PMBoK®, this step was included into the risk analysis process. Also, there was a semi-qualitative analysis, within the PMI s qualitative analysis process that was an explicit step within the AS/NZS standard.